Influence of endosymbionts on the reproductive fitness of the tick Ornithodoros moubata - Taraveau, Florian; Pollet, Thomas; Duhayon, Maxime; Gardès, Laëtitia; Jourdan-Pineau, Hélène (Peer Community Journal)

(untitled)
Over the past decade, many studies have demonstrated the crucial role of the tick microbiome in tick biology. The soft tick Ornithodoros moubata is a hematophagous ectoparasite of Suidae, best known for transmitting the  African swine fever virus. Its bacterial microbiota is characterized by a high prevalence of Francisella-like and Rickettsia endosymbionts. The present study aims to better understand the potential influence of these two major members of the tick microbiota on the reproductive fitness of O. moubata. A total of 132 adult female ticks were treated with antibiotics using gentamycin or rifampicin added to the blood meal. Half of the ticks were also supplemented with B vitamins to address the nutritional role of endosymbionts. Over two periods of 50 days, several traits related to the reproductive fitness were monitored to investigate the importance of Francisella and Rickettsia for these traits. It appeared that most of the reproductive parameters considered were not affected. However, antibiotic treatments induced an increase in the tick survival, indicating a potential fitness cost of harboring endosymbionts during the tick reproductive cycle. Similarly, 366 first stage nymphs of O. moubata were exposed to the same treatments for molecular quantification of both endosymbionts. Results from qPCR suggested that the treatments had a bacteriostatic effect on endosymbionts without completely eliminating neither Francisella-like endosymbiont nor Rickettsia.